Factors Related to Patient Expectation and Satisfaction among New and Existing Denture wearers with Complete Denture therapy - Pandey, A (Journal of Nepalese Prosthodontic Society, 2020)
Introduction: Edentulism is considered a debilitating condition with aging in which several dental and non-dental factors play a vital role in the success of prosthodontic treatment. Patient satisfaction is an important non-dental component. The dentist should aim for functional rehabilitation by satisfying the patient medically, functionally, and psychologically. Patient satisfaction depends on two factors: patient factor and dentist factor. From the patient’s view, satisfaction is guided by improved quality with factors like eating, easy communication, comfort, social life, economic status, and vocational opportunities. From dentist’s view, treatment options, treatment cost etc. affects the patient’s satisfaction.Materials and Methods: Experimental study conducted in Department of Prosthodontics, College of Medical Sciences, Bharatpur in patients receiving complete denture by convenience sampling in six months duration in sixty-five samples. Questionnaires regarding patient’s expectations and satisfaction in terms of retention, mastication, phonetics, esthetics, and comfort were used in both 1st-time denture wearer and existing denture wearer was recorded. Grading was rated with Visual Analog Scale (VAS) from 0 to 10 using the optimum cutoff values. Data were recorded in SPSS 21 and analyzed.Results: Independent t-test was carried out for expectation showing a statistically significant difference between retention, mastication, aesthetics, phonetics, comfort, and denture status with p value 0.036, 0.00, 0.001, 0.003, and 0.013 respectively. Statistically, a significant difference was found for satisfaction between aesthetics and denture status with a p-value of 0.01.Conclusions: Expectation and satisfaction were found to be more in first-time denture wearers than existing denture wearers. Experiences obtained beforehand with complete dentures could influence patient expectations and satisfaction.